2007
DOI: 10.1371/journal.pone.0000773
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in the Thermotolerance of Neural Function and Behavior due to a cGMP-Dependent Protein Kinase

Abstract: Although it is acknowledged that genetic variation contributes to individual differences in thermotolerance, the specific genes and pathways involved and how they are modulated by the environment remain poorly understood. We link natural variation in the thermotolerance of neural function and behavior in Drosophila melanogaster to the foraging gene (for, which encodes a cGMP-dependent protein kinase (PKG)) as well as to its downstream target, protein phosphatase 2A (PP2A). Genetic and pharmacological manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
(46 reference statements)
2
63
0
Order By: Relevance
“…In locusts, in addition to the high PKG activity reported here, the gregarious phase is characterized by high levels of lipid reserves, higher hiperlipaemic response to flight, and increased adipokinetic response (mediated by CC neurohormones; Pener, 1992, 1995;Ayali et al, 1996;Pener et al, 1997). PKG signaling also plays a role in modulating environmental stresses, such as thermal stress (in D. melanogaster, Dawson-Scully et al, 2007). Phase differences are also related to thermotolerance in locusts, including, for example, expression of heat shock proteins (Wang et al, 2007) and response to pathogens (Elliot et al, 2003(Elliot et al, , 2005.…”
Section: Discussionmentioning
confidence: 74%
“…In locusts, in addition to the high PKG activity reported here, the gregarious phase is characterized by high levels of lipid reserves, higher hiperlipaemic response to flight, and increased adipokinetic response (mediated by CC neurohormones; Pener, 1992, 1995;Ayali et al, 1996;Pener et al, 1997). PKG signaling also plays a role in modulating environmental stresses, such as thermal stress (in D. melanogaster, Dawson-Scully et al, 2007). Phase differences are also related to thermotolerance in locusts, including, for example, expression of heat shock proteins (Wang et al, 2007) and response to pathogens (Elliot et al, 2003(Elliot et al, , 2005.…”
Section: Discussionmentioning
confidence: 74%
“…Pharmacologically or genetically reducing levels of PKG, or its downstream targets, increases thermotolerance of the larval Drosophila neuromuscular junction. Similar treatments also increase the locust vCPG's tolerance to heat stress (Dawson-Scully et al, 2007), suggesting evolutionary conservation of the mechanism. Hyperthermic arrest of vCPG operation in the locust CNS is associated with SDlike increases of [K ϩ ] o that occur before irreversible cellular collapse (Rodgers et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Are sitters more plastic than rovers across environmental contexts, or does it depend on the type of adversity (e.g., nutritional, social) the individual experiences, and the timing of that adversity (chronic acute) during development? Previous studies have shown that sitters are more resistant to acute abiotic stressors, such as heat and hypoxia, than are rovers (69)(70)(71). The type of exposure used, chronic or acute, may explain which variant exhibits plasticity.…”
mentioning
confidence: 99%